KONSEP, IDENTIFIKASI, ALAT ANALISIS DAN MASALAH PENGGUNAAN VARIABEL MODERATOR - Sugiono Sugiono (Faculty of Economics and Business Diponegoro University, 2012)
ABSTRACT This article is presented to comprehend theory, concept and analysis tools in using moderating variable. Stipulating a theory, concept will affect at usage or election of analysis tools. Therefore, this matter suggests researchers have to select tool of analysis that most precise. Some approach to be elaborated, for example, Interaction Approach, Absolute Difference Value Approach, Residual and of Subgroup Approach. The major problem of the operation and identification of moderator variables are discussed. Classification of moderating variable can be based on the relationship with the criterion variable, that is, whether the specification variables are relate or not relate to the criterion variable and whether the specification variables interacts with the predictor variable. It will be discussed also at least four problems of competent to get attention when use moderator variable. Keywords: moderating variabel; interaction approach; classification of moderating varible